Microwave-Assisted Synthesis of 3,5-Dibenzyl-4-amino-1,2,4-triazole and its Diazo Ligand, Metal Complexes Along with Anticancer Activity - Anjali Jha; Y. L. N. Murthy; G. Durga; T. T. Sundari (E-Journal of Chemistry)
Synthesis of 3,5-dibenzyl-4-amino-1,2,4-triazole was accomplished via a conventional method as well as microwave irradiation method, followed by diazotization and coupling with 2,4-pentanedione. The dinucleating ligand was isolated and complexed with Ni(II), Cu(II) and Ru(III) chlorides. These complexes were screened on Jurkat, Raji & PBMC cell lines for anticancer activity. Ruthenium complexes showed potential anticancer activities.